AN OUTCOME-BASED INTERNATIONALISATION STRATEGY FOR THE ISLAMIC EDUCATION MANAGEMENT DEGREE PROGRAMME: ENHANCING GLOBAL RECOGNITION THROUGH CURRICULUM STANDARDISATION, QUALITY ASSURANCE AND RESEARCH PRODUCTIVITY AT UIN IMAM BONJOL PADANG - Hasnawati Hasnawati; Najmi Diyana Lathifah; Intan Nur’aini Rasyidah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The internationalisation of Islamic higher education is a strategic priority for enhancing global recognition, academic reputation, international mobility and the competitiveness of graduates. However, in many Islamic Education Management programmes, internationalisation is still often understood as merely administrative and symbolic activities—such as signing international cooperation agreements, organising international seminars or academic visits—without being accompanied by systematic measurement of outcomes. This article aims to formulate an outcome-based internationalisation strategy for the Islamic Education Management Programme at UIN Imam Bonjol Padang through the integration of curriculum standardisation, quality assurance, and research productivity. This research employs a qualitative approach using a case study design. Data were collected through in-depth interviews, and an analysis of curriculum documents, quality assurance documents, cooperation agreements, research roadmaps, and lecturers’ publication reports. Analysis was conducted through data reduction, thematic coding, categorisation, triangulation of sources, and the development of a conceptual model. The findings indicate that outcomes-based internationalisation requires a shift from an activity-oriented approach to one focused on measurable academic achievements. Curriculum standardisation serves as the foundation for strengthening global relevance through the alignment of learning outcomes, the integration of global Islamic education issues, bilingual classes, and credit transfer opportunities. Quality assurance functions as an accountability mechanism that ensures internationalisation is documented, evaluated, and continuously improved. Research productivity is a key instrument in enhancing international academic visibility through reputable publications, research collaborations, citations, and global academic networks. The novelty of this article lies in the development of an outcomes-based internationalisation model at the degree programme level, specifically for the Islamic Education Management programme at UIN Imam Bonjol Padang, which integrates three strategic pillars as instruments for enhancing the global recognition of Islamic higher education.